(untitled) (AUN INTERNATIONAL CONFERENCE, 2024)
This review explores the risks associated with digital instructional practices, focusing mainly on the implications of cyber threats in higher education digitally connected classrooms and society. Although advancements in technology have enabled the development and use of diverse and adaptable teaching methods and societal endeavours, their impact during and after COVID-19 has also introduced or escalated cyber threats in higher education digitally connected classrooms and society, necessitating a review of approaches to teaching, learning and social engagements in today’s digitally rich environment. This review aims to identify the cyber threats confronting digitally connected higher classrooms and society, revealing their various forms in higher education or social environments. This review underscores the importance of continuous engagement with educators, students, parents and social awareness programs as part of addressing cyber threats in higher education and society. The author concludes by offering valuable insights to help shape resilient digitally connected higher instructional systems in Nigeria.